2013
DOI: 10.1089/thy.2013.0102
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Risk Impact of Five Genetic Variants Associated with Papillary Thyroid Carcinoma

Abstract: Background: Two recent genome-wide association studies (GWASs) identified five single nucleotide polymorphisms (SNPs; rs965513, rs944289, rs966423, rs2439302, and rs116909374) associated with papillary thyroid carcinoma (PTC). Each variant showed highly significant but moderate to low disease risk. Here we assessed the cumulative risk and predictive value of the five SNPs. Methods: We genotyped two cohorts of individuals, 747 PTC cases and 1047 controls from Ohio and 1795 PTC cases and 2090 controls from Polan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 38 publications
(52 reference statements)
5
67
0
Order By: Relevance
“…8 (4). The association between rs965513 and thyroid cancer risk has been independently confirmed in different populations (5)(6)(7)(8)(9)(10)(11). The association was also observed in familial PTC and in patients with radiation-induced PTC (12)(13)(14)(15).…”
mentioning
confidence: 71%
“…8 (4). The association between rs965513 and thyroid cancer risk has been independently confirmed in different populations (5)(6)(7)(8)(9)(10)(11). The association was also observed in familial PTC and in patients with radiation-induced PTC (12)(13)(14)(15).…”
mentioning
confidence: 71%
“…Several germline changes have been reported to predispose to DTC, including variants in microRNA-146a, ATM-CHEK2-BRCA1 pathway, TERT gene, and 5 SNPs pinpointed by GWAS study (2)(3)(4)(5)(12)(13)(14)(15). So far, no study revealed the influence of germline (inherited) variants on the overall mortality of patients with thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we revealed a cumulative, additive effect of rs116909374, rs965513, rs944289, rs966423, and rs2439302 on the thyroid cancer risk (4). Because the influence of polymorphic variants on the overall survival has never been established, we analyzed the association of these SNPs with the mortality of patients with thyroid cancer.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations